PENINGKATAN WAWASAN PETANI DENGAN INPUT TEKNOLOGI MELALUI ZPT (ZAT PENGATUR TUMBUH) ALAMI DARI KEONG MAS - Mulyanti; Sri Rahayu; Dewi Yana (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2023)
Fertilizer is material that is put into the soil to provide nutrients for plant growth and development. Based on the source of the materials used, fertilizers can be separated into inorganic fertilizers and organic fertilizers. Furthermore, organic fertilizer is divided into two, namely liquid fertilizer and solid fertilizer. One of the raw materials for making natural growth regulators that comes from animals is the golden snail (Pomaceae canaliculata). Golden snails are animals that have a high protein content. The meat and shell of golden snails contain protein, fat, carbohydrates, Na, K, riboflavin, Niacin, Mn, C, Cu, Zn and Ca. Activities in the Gue village community, Kuta Baro District, Aceh Besar Regency are still very lacking, this is due to several problems, namely the lack of farmers attending training or seminars on agricultural cultivation, Still using synthetic Fertilizers and ZPT, Mas snails as pests on plants are only used as feed additional livestock while the rest are destroyed with synthetic pesticides. Never received counseling about the use of golden snails to make natural ZPT and liquid organic fertilizer. Low interest in the younger generation to take part in agriculture. Implementation of activities is carried out in 2 (two) activity stages. Stage one provides education and explanations about growth regulators and indoor golden snails. The second stage is to practice making growth regulators from golden snails in an open space. The location for this community service is in Gue village which will last for 6 days in December 2022. The people of Gue village are very enthusiastic about implementing science and technology activities for the community, already understand how to make liquid organic fertilizer from golden snails, and really understand the benefits of organic fertilizer liquid from golden snails on soil fertility and how to administer it to cultivated plants.